Composition and abundance model of phytoplankton in water of Ciliwung River, Jakarta - MELATI FERIANITA FACHRUL; SETIJATI HARTINAH EDIYONO; MONIKA WULANDARI (Biodiversitas Journal of Biological Diversity, 2008)
The research was conducted in Ciliwung River, from Bogor until Jakarta. The aims of this research were to (i) identify the species of phytoplankton were occupied in the Ciliwung River and (ii) determine the river ecosytem condition using ecological modeling by composition and distribution of abundance model. This research was conducted in two period sampling which on July 2005 (1st period) and August 2005 (2nd period). The river ecosystem was devided into three segments, which covered 10 stations, namely: Cisarua, Gadog, Kedung Halang (Segment I), Kelapa Dua, Kalibata, Kampung Melayu, Guntur (Segment II), Pejompongan, K.H. Mas Mansyur, and Teluk Gong (Segment III). The result on the first period obtained 4 divisions that consist of 41 species, such as 12 species from Cyanophyta, 25species from Chlorophyta, 4 species from Chrysophyta and 1 species from Euglenophyta. Thus, from the second period, obtained 4 divisions that consist of 45 species, such as 8 species from Cyanophyta, 28 species from Chlorophyta, 5 species from Chrysophyta and 4 species from Euglenophyta. The result of analysis on phytoplankton abundance distribution showed that, both on first and second periodsan appropriate model is Motomura Model.Key words: composition, abundance model, phytoplankton, Ciliwung River.